Stigmas, Work and Organizations (Palgrave Explorations in Workplace Stigma,, 2018)
This book brings together current research on stigma, stigma management, and stigma theory as applied to business and management at the micro, meso, and macro levels. It provides a comprehensive perspective of the literature on stigmas and is relevant to those working in organizational behavior, human resource management, and management studies more broadly. The book includes chapters covering topics at the individual level (e.g., religious belief, illness, obesity, and sexual preference), occupational level (e.g., healthcare workers, garbage collectors, butchers, medical doctors), and organizational level (e.g., organizational image, multinational organizations). It offers readers a truly international perspective on this growing area of study.